É possível romper com a herança ibérica? Uma releitura da obra de Raymundo Faoro - Marcos Abraão Fernandes Ribeiro (Ciências Sociais Unisinos, 2019)
In this article we propose a view of the work of Raymundo Faoro through the questioning of his most influential interpretations, produced by Luiz Werneck Vianna, Juarez Guimarães and Rubens Goyatá Campante. To do so, we return to Faoro’s view of the emergence of modernity and its reinterpretation of the Weberian diagnosis. These actions are funda- mental for the author to construct his essentialist theory about the civilization formed in Portugal and inherited by Brazil. Emphasizing points not systematically explored, we argue that Faoro’s theory has the material evolutionism as its structuring element which, by postulating the necessary relation between feudalism and capitalism as the only authentic path to the institution of modernity, makes it impossible to rupture any nature. Thus, his theory ends up reproducing an irreversible gap between the intellectual and the political sides. With this analysis, we try to bring new elements to reinterpret one of the most important Brazilian intellectuals, whose theses on the conduct of the State are still being addressed to us today.